A7.01 Abrogation of collagen-induced arthritis by a second generation peptidyl arginine deiminase inhibitor is associated with a shift from TH1/TH17 to TH2-mediated immune responses. (24th February 2016) - Kawalkowska, J; Quirke, AM; Ghari, F; Subramanian, V; Li, R; Thompson, PR; Williams, RO; Fischer, R; Thangue, NB La; Venables, PJ
Abstract : Citrullination is catalysed by peptidylarginine deiminases (PADs) and may play a role in joint inflammation by generating proteins recognised by autoantibodies and/or by targeting histones and thereby modulating gene transcription. The PAD inhibitor Cl-amidine was shown to have a modest anti-inflammatory effect in collagen-induced arthritis (CIA), when given prophylactically at high doses. While much of this benefit was thought to be due to PAD4 inhibition, recent studies have highlighted the pro-inflammatory effects of PAD2. The objective of this study was to assess the therapeutic potential BB-Cl-amidine, which is 10 fold more active than Cl-amidine against PAD2. We chose CIA as a reproducible model of immune-mediated arthritis and used a clinically-relevant therapeutic protocol, in which mice were treated after disease onset. CIA was induced in DBA/1 mice by immunisation with bovine type II collagen. After disease onset, mice were treated daily with vehicle or BB-Cl-amidine (10 mg/kg, n = 12). On day 10, mice were culled, and paws, blood and lymph nodes collected for further analysis. In serum, cytokines were measured using a multiplex platform and anti-citrullinated peptide antibodies (ACPA) by ELISA. The phenotypes of T cells were determined by FACS. Citrullinated proteins were identified by mass spectrometry. Treatment of arthritic mice with BB-Cl-amidine, resulted in a significant reduction in clinical scores and paw swelling. Histological changes in joints were almost completely normalised by BB-Cl-amidine. Unexpectedly, while pro-inflammatory cytokine (TNF-α, IL-1β, IL-6) levels in serum remained unaffected by BB-Cl-amidine, IL-4, IL-5 and IL-10 levels were significantly elevated. In line with this, IL-4-expressing Th2 cells were increased in the lymph nodes of BB-Cl-amidine treated mice. Further analysis revealed a decrease in Th1 and Th17 numbers with BB-Cl-amidine. In addition BB-Cl-amidine reduced histone H3.2 citrullination, with little affect on the ACPA response which suggests that BB-CL-amidine may inhibit gene expression in disease via an epigenetic mechanism. In conclusion, BB-Cl-amidine is therapeutic in CIA due to immunomodulation rather than immunosuppression and supports anti-inflammatory Th2-type, while inhibiting pro-inflammatory Th1/Th17-type responses. We propose that these effects are mediated by transcriptional regulation and that targeting PADs is a realistic strategy for the treatment of chronic inflammatory diseases.